The Use of Peer Feedback to Enhance Vocabulary Mastery of Eleventh-Grade Students at SMA Negeri 1 Palasa - Rosmala Usman; Sriati Usman; Abraham Eisenring; Abd. Kamaruddin (MASI Mandiri Edukasi, 2026)
This research was conducted to address the persistent issue of limited vocabulary mastery among eleventh-grade students at SMA Negeri 1 Palasa. Vocabulary is a key component of language proficiency, and effective strategies such as peer feedback are increasingly emphasized to support students’ independent learning. The study aimed to determine whether implementing Peer Feedback could effectively improve their vocabulary achievement. To investigate this objective, the study employed a quasi-experimental design involving two groups: an experimental group of 20 students who received instruction through Peer Feedback and a control group of 22 students who were taught using conventional methods. This study focused on action verbs and common nouns. A vocabulary test was administered as both a pre-test and post-test, and the collected data were analyzed statistically to identify differences in students’ performance before and after the treatment. The findings show that the experimental group improved from a mean pre-test score of 44.83 to a post-test score of 66.15, whereas the control group improved from 48.94 to 58.31. Furthermore, the t-test result (t = 5.17; p = 0.05) indicates that Peer Feedback use had a significant positive effect on students’ vocabulary mastery. Based on the results, the study concludes that Peer Feedback is an effective instructional strategy for enhancing vocabulary mastery among EFL learners at the senior high level, and integrating it into classroom activities can further support active learning and strengthen students’ vocabulary development.